In vitro antioxidant, cholinesterase and tyrosinase inhibitory activities of calophyllum symingtonianum and calophyllum depressinervosum (guttiferae) - Aminudin, Nurul Iman; Ahmad, Farediah; Bakhtiar, M. Taher (Coastal Life Medicine Media co., Limited, 2015)
Objective: To screen the antioxidant, cholinesterase and tyrosinase enzymatic inhibition activities of the leaves and heartwood of Calophyllum symingtonianum (C. symingtonianum), and the bark of Calophyllum depressinervosum (C. depressinervosum). Methods: Samples of leaves and heartwood of C. symingtonianum and bark of C. depressinervosum were tested for their total phenolic content and in vitro antioxidant assay by 2,2-diphenyl-1-picrylhydrazyl radical scavenging and β-carotene bleaching. Cholinesterase inhibition by Ellman’s method and tyrosinase inhibition using L-3,4-dihydroxyphenylalanine as a substrate were also tested. Results: All methanol extracts were found to exhibit strong 2,2-diphenyl-1-picrylhydrazyl radical scavenging effects. Extracts from the heartwood of C. symingtonianum gave a low IC50 (5.17±0.04) μg/mL followed by bark of C. depressinervosum [(7.30±0.14) μg/mL] and C. symingtonianum leaves [(15.70±1.43) μg/mL]. The methanol extract of C. depressinervosum bark showed 95.08% inhibition of β-carotene bleaching. All extracts showed moderate inhibition towards tyrosinase activity with an IC50 of more than 100 μg/mL. The methanol extract of C. depressinervosum stem bark showed the highest inhibition (78.46%) against butyrylcholinesterase. Conclusions: These results showed that both Calophyllum species are potential sources of antioxidant and cholinesterase inhibitors. Further study is needed for the isolation and characterization of the active metabolites responsible for both activities.